Importance of adding DNA to the database for identification of sexual criminals (Research, Society and Development, 2023)
Biogenetics plays a key role in solving sexual crime cases as it provides powerful tools for identifying criminals and obtaining solid forensic evidence. The purpose of this study was to understand the improvement and process of identifying sexual offenders, through the inclusion of DNA information in a database, with the aim of increasing the effectiveness of investigations and the prevention of crimes of this nature. To achieve these goals, data regarding the importance of this approach was gathered and analyzed, promoting greater awareness about the relevance of collecting DNA samples to strengthen research capacity. Effective information sharing strategies between different law enforcement agencies, laboratories and research institutions were examined and suggested. Collaboration and data exchange played a crucial role in optimizing the identification of sex offenders, ensuring that valuable information was shared and used effectively. With the achievement of these objectives, the aim is to gather knowledge with the aim of strengthening the criminal justice system in combating sexual crimes, providing significant advances in this area.